UJI AKTIVITAS ANTIKOLESTEROL HASIL FERMENTASI ANGKAK PADA TIKUS GALUR Sprague dawley - Abdul Rahman Wahid; Armiyatin Damayanti; Alvi Kusuma Wardani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Hypercholesterolemia is a condition in which the levels of cholesterol in the blood increases and decreases in HDL cholesterol levels below the normal range. Low levels of HDL cholesterol and high levels of LDL cholesterol can increase the risk of atherosclerosis. Angkak is a fermented product from brown rice using mold Monascus purpureus. Angkak contains secondary lovastatin which functions as an anti-cholesterol. This study aims to determine the effect of the administration of brown rice Angkak to decreasing LDL levels at a dose of 15 mg/200gBB, 40 mg/200gBB, and 65 mg/200gBB in mice induced by high cholesterol feed. This type of research is true experimental laboratory withmethods pre and post test control group design. The results showed that Angkak dosages of 15 mg / 200gBB, 40 mg / 200gBB, and 65 mg / 200gBB were able to reduce levels in rats induced high cholesterol. The conclusion of this study is that red rice Angkak containing lovastatin has an anticolesterol effect on decreasing total cholesterol, LDL, and trigliseride levels in rats.